Skrining Bakteri Dekomposer Sebagai Penghilang Bau Kotoran Ayam - Nika Ropiatningsuari; Suryo Wiyono; Suryahadi Suryahadi (Bumi Lestari Journal of Environment, 2018)
The decomposition of chicken excreta produce odorous gases, that case environmental pollution. One of alternative technique to reduce the odorous gases is by applying specific bacteria. The aim of this study was to obtain bacterial isolates that capable of reducing NH3 and H2S production and odors. Decomposer bacterial candidates were isolated from chicken manure, guano, and peat soil. Selection of isolates of oxidizing bacteria is carried out using selective media. All isolates that were found from chicken manure, guano, and peat soil tested for hypersensitive reaction on tobacco and hemolysis on blood agar. The isolated bacteria that showed negative HR and HL responses than used for a further experiment. Five isolates of bacteria which reduce odors based on organoleptic test were WiK 15, TnK 7, WiGu 11, CGu 7 and MaGa 5. NH3 and H2S from decomposition chicken excreta were analyzed by spectrophotometric and colorimetric method. The average of total NH3 production from seven days observation showed ranged level from 1.09 ppm to 1.77 ppm, while total H2S gas production ranged from 15.05 to 16.57 ppm. Bacterial isolate CGU 7 showed make lowest total production of NH3.